當m>1時,(1-m)(m-1)≥2,無解;
當m≤1時,(1-m)(1-m)≥2,解得m≤1-
2 |
所以m≤1-
2 |
(2)由于m>0,x≥m.
所以h(x)=3x+
m2 |
x |
任取m≤x1≤x2,h(x2)-h(x1)=(x2-x1)(
3x1x2-m2 |
x1x2 |
x2-x1>0,3x1x2-m2>3m2-m2>0,x1x2>0
所以h(x2)-h(x1)>0即:h(x)在[m,+∞)為單調(diào)遞增函數(shù).
(3)、①m<1時,x∈[1,2],f(x)=2x2+(x-m)(x-m)=3x2-2mx+m2,
h(x)=
f(x) |
x |
即:g(x)=3x2-(2m+1)x+m2≥0
由于y=g(x)的對稱軸為x=
2m+1 |
6 |
故g(x)在[1,2]為單調(diào)遞增函數(shù),
故g(1)≥0∴m2-2m+2≥0.
所以m<1.
②當1≤m≤2時,h(x)=
|
易證y=x-
m2 |
x |
由②得y=3x+
m2 |
x |
所以,h(1)≥1,即0≤m≤2,
所以1≤m≤2.
③當m>2時,h(x)=x-
m2 |
x |
綜上所述m≤2.